2002
DOI: 10.1007/s00418-002-0423-1
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric contractions leading to DOMS do not cause loss of desmin nor fibre necrosis in human muscle

Abstract: High force eccentric muscle contractions can result in delayed onset muscle soreness (DOMS), prolonged loss of muscle strength, decreased range of motion, muscle swelling and an increase of muscle proteins in the blood. At the ultrastructural level Z-line streaming and myofibrillar disruptions have been taken as evidence for muscle damage. In animal models of eccentric exercise-induced injury, disruption of the cytoskeleton and the sarcolemma of muscle fibres occurs within the first hour after the exercise, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
57
1
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 42 publications
9
57
1
2
Order By: Relevance
“…Consequently, we question the importance of inflammation to the adaptation process after eccentric exercise in humans. In that sense, our findings are in agreement with other human studies where signs of myofibrillar remodelling have been observed, without leukocytes detectably present during the first days after eccentric exercise (Feasson et al, 2002;Yu et al, 2002).…”
Section: Nsaids Inflammation and The Repeated-bout Effectsupporting
confidence: 94%
“…Consequently, we question the importance of inflammation to the adaptation process after eccentric exercise in humans. In that sense, our findings are in agreement with other human studies where signs of myofibrillar remodelling have been observed, without leukocytes detectably present during the first days after eccentric exercise (Feasson et al, 2002;Yu et al, 2002).…”
Section: Nsaids Inflammation and The Repeated-bout Effectsupporting
confidence: 94%
“…Our morphological findings are consistent with previous findings in human experiments (Yu et al, 2002), although recently Koskinen et al (2006) have found some loss of dystrophin from human subjects after eccentric actions. The diverse occurrence in morphological damage of muscle tissue in animal and human studies can probably be explained by the nature of the exercise.…”
Section: Discussionsupporting
confidence: 94%
“…This is not always the case in human studies. Yu et al (2002) did not recognize sarcolemmal disturbance, loss of desmin or muscle cell degeneration after eccentric muscle actions. Recently Koskinen et al (2006) have observed some loss of dystrophin also in some human subjects after eccentric actions.…”
mentioning
confidence: 85%
“…In contrast, studies on humans after voluntary eccentric exercise revealed no [5], [6], [20], [21], [22], [23] or only minor damage [10], [24] in muscle fibre membrane. To our knowledge, no data is available in humans with regard to the initial reactions of muscle fibre membrane to acute voluntary eccentric exercise.…”
Section: Introductionmentioning
confidence: 77%
“…Passive manipulation and active movement alter intramuscular pressure and stimulate mechanoreceptor nerve endings, contributing to the perception of soreness [4]. However, recent studies in humans provided evidence which did not support the hypothesis, e.g., voluntary eccentric exercise did not lead to desmin intermediate filament network hydrolysis [5], [6], myofibrillar disruption [5], [7] or muscle fibre inflammation and necrosis [5], [6], [8], [9], [10]. The Z-band streaming, classically proposed to be a hallmark of muscle damage after eccentric exercise [11], [12] was also proved to represent myofibril remodelling [7], [13], [14], [15], [16].…”
Section: Introductionmentioning
confidence: 99%